2020
DOI: 10.1021/acs.jafc.0c01020
|View full text |Cite
|
Sign up to set email alerts
|

Possible Insecticidal Mechanism of Cry41-Related Toxin against Myzus persicae by Enhancing Cathepsin B Activity

Abstract: Cry toxins produced by Bacillus thuringiensis are well known for their high insecticidal activities against Lepidoptera, Diptera, and Coleoptera; however, their activities against Aphididae are very low. Recently, it has been reported that a Cry41-related toxin exhibited moderate activity against the aphid Myzus persicae, and thus, it is highly desirable to uncover its unique mechanism. In this paper, we report that Cathepsin B, calcium-transporting ATPase, and symbiotic bacterial-associated protein ATP-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 57 publications
0
29
0
Order By: Relevance
“…To identify Cry7Ab4-binding proteins in M. persicae, pull-down and liquid chromatography tandem mass spectrometry (LC–MS/MS) assays were carried out as described previously. , In brief, 1 mL of active Cry7Ab4 toxic core (0.5 mg/mL) was incubated with a pre-equilibrated Sepharose 4B beads (0.5 mol/L NaCl, 0.1 mol/L NaHCO 3 , pH 8.3) (GE Healthcare, USA) at 4 °C for 12 h. Subsequently, 25 μL of Cry7Ab4-coupled Sepharose 4B matrix was incubated with 50 μL of M. persicae homogenate (200 fourth instar M.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To identify Cry7Ab4-binding proteins in M. persicae, pull-down and liquid chromatography tandem mass spectrometry (LC–MS/MS) assays were carried out as described previously. , In brief, 1 mL of active Cry7Ab4 toxic core (0.5 mg/mL) was incubated with a pre-equilibrated Sepharose 4B beads (0.5 mol/L NaCl, 0.1 mol/L NaHCO 3 , pH 8.3) (GE Healthcare, USA) at 4 °C for 12 h. Subsequently, 25 μL of Cry7Ab4-coupled Sepharose 4B matrix was incubated with 50 μL of M. persicae homogenate (200 fourth instar M.…”
Section: Methodsmentioning
confidence: 99%
“…The target bands were excised from a silver-stained gel and identified by LC–MS/MS (BGI Genomics, Shenzhen, China). LC–MS/MS data were searched as described previously …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous work has identified proteins from midgut juice that bind to Cry toxins, and these non-receptor proteins also affect insecticidal activities of Cry toxins ( 16 18 ). It has been reported that Cry toxin receptors in P. xylostella , including ALP and ABCC, are regulated by the MAPK signal pathway, and a high level of hormones promotes the expression of ALP and ABCC by activating the MAPK pathway, leading to Cry resistance ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…2005) were reported to be Cry1Ab1-binding proteins in the midgut juice of Plutella xylostella, and Peroxidase-C was a Cry1Ab-binding protein in Spodoptera exigua (Lu et al 2017). Zhao et al found that Cry41-realted interacted with Cathepsin B and enhanced its activity, causing acceleration of apoptosis of aphid cells (Zhao et al 2020). Additionally, galectin-14 was reported to compete with Cry11Aa for binding to BBMVs and ALP1 in Aedes aegypti to prevent effective binding of the toxin to receptors (Zhang et al 2018).…”
Section: Introductionmentioning
confidence: 99%